Anesthesia and analgesia in laboratory animals. - Fish, R. E. (Richard E.) (American College of Laboratory Animal Medicine series., 2008)
Since the publication of the first edition, interest in the field has continued to rise, most notably in pain management. Anesthesia and Analgesia in Laboratory Animals focuses on the special anesthetic, analgesic, and post-operative care requirements associated with experimental surgery. Fully revised and updated this new edition provides the reader with agents, methods, and techniques for anesthesia and analgesia that ensure humane and successful procedural outcomes. * New to this edition - Section V which deals with new issues covering pain research, ethical issues, legal issues, and imaging studies. S * New to this edition - Section IV now includes chapters on ferrets, birds, reptiles, amphibians, fish, and invertebrates. *.